La Collaboration des arsenaux bretons sous l’Occupation - Lars Hellwinkel (L'Atelier du CRH)
With the occupation of the French coasts in the summer of 1940, the German Navy not only obtained a direct access to the Atlantic, but also took possession of the arsenals of Brest, Lorient and Cherbourg. Focusing on the two arsenals in Britanny, the article highlights the integration of French naval arsenals into Germany’s naval war strategy against Great Britain and outlines the role of the Vichy regime’s Navy in the military collaboration of France with the Third Reich